Induction of apoptosis by fungal extracts HAB10R12 and HAB14R3 against colon (HCT116) cancer cell lines / Nurhayati Abd Samad - Abd Samad, Nurhayati (2007)
Natural products play an extremely important role as the major source of drugs used for cancer treatment. Endophytes, a new source of natural products, are microorganisms that reside in the living tissues of the host plant and may produce substances that have potential to be used in modern medicine. This study aims to determine the cytotoxic activity of endophytic extracts (HAB10R12 and HAB14R3) against colon (HCT116) cancer cells. The mode of cell death elicited by HAB10R12 and HAB14R3 and apoptotic related genes involved in the cell death were also investigated. The endophytic fungi were subcultured on half strength PDA agar and extracted with ethyl acetate. The cytotoxic activities of the extracts against HCT116 were evaluated using the MIT assay. Cell death detection was carried out using Cell Death Detection ELISAPLUS. The results from present study showed that the cytotoxic activity (IC50) of the extracts were 0.055µg/ml for HAB10R12 and 0.056µg/ml for HAB14R3.The results also indicated that the mechanism of cell death elicited by extracts against HCT116 were mainly due to apoptosis. The HAB14R3 exhibited better apoptotic activity when compared to HAB10R12. The study of apoptotic related genes however, was inconclusive. PCR methods needs to be optimised to confirm the expression of gene related to the apoptotic pathway. In future, more studies also should be conducted with pure compounds of HAB10R12 and HAB14R3 in the future to discover the other potentials possess by these endophytic fungi.